Intervensi Modul Penyelenggaraan Makanan terhadap Pengetahuan dan Sikap Pengolah Makanan Di Pondok Pesantren Kota Kendari - Euis Nurlaela; Sri Yunanci V Gobel (Poltekkes Kemenkes Kendari, 2020)
One of the efforts to maintain the nutritional status of students, the boarding school needs to maintain and increase the consumption to remain adequate in the process of organizing the food. This research aims to determine the influence of the design of the companion module on food Implementation guidelines on the knowledge and attitude of food processing personnel in the boarding school in Kendari City. This type of research is an analytical survey with the design quasi experiment with one group pre-test post-test which is the food processing force group of 48 people observed before the intervention with pre-test and after intervention (mentoring using modules for 2 days/week for 1 month) with post-test I (after training) and post-test II (after 1 month of training). The results of knowledge level statistical test and attitude of food processing personnel are known between before, after the training (post-test I) and 1 month after training (post-test II) obtained the p-value 0,000 (P < 0.05) can be concluded that there is a difference in knowledge and attitude of food processing personnel before and after the mentoring using the Food maintenance module.